The feasibility of mitral valve device foldoplasty: an in vivo study to evaluate durable retention. (12th August 2021) - Wamala, Isaac; Saeed, Mossab Y; Hammer, Peter E; Bautista-Salinas, Daniel; Gauvreau, Kimberlee; Ghelani, Sunil J; Vasilyev, Nikolay V; del Nido, Pedro J
Abstract : Degenerative mitral valve (MV) disease is a frequent cause of primary mitral regurgitation (MR) [1]. Abstract:  : OBJECTIVES: We have previously shown in experimental settings that a leaflet foldoplasty device reduces redundant leaflet area to re-establish mitral valve (MV) coaptation. The current study investigates the in vivo device retention and functional durability following foldoplasty. METHODS: The prototype is of superelastic nitinol formed into a 3-dimensional shape. It is unfolded to engage a specified area of leaflet tissue and then folded to exclude this tissue from the coaptation surface. Design modifications were made and tested in benchtop studies to determine the optimal design for durable retention within the leaflet. To evaluate in vivo performance, posterior leaflet chordae were severed in Yorkshire pigs to produce complete posterior leaflet prolapse and severe mitral regurgitation. Design modifications were then used for MV repair. Five animals that underwent repair using the optimal design were observed for 2 weeks postoperative to evaluate the functional result and implant retention. RESULTS: Device position and orientation were maintained at 2 weeks while preserving the functional MV repair in all 5 animals. Coaptation height was 5.5 ± 1.5 mm, which was not significantly different from a baseline of 4.9 ± 0.8 mm. The degree of leaflet excursion was 41.0 ± 16.0 compared to a baseline of 58.7 ± 27.5. CONCLUSIONS: Device foldoplasty is a new concept for MV repair based on the reduction of redundant leaflet tissue area. This study demonstrates the feasibility of safe maintenance of this repair without early dislodgement or embolization.